Dementia prevalence estimation among the main ethnic groups in New Zealand: a population-based descriptive study of routinely collected health data. Issue 9 (7th September 2022) - Cheung, Gary; To, Edith; Rivera-Rodriguez, Claudia; Ma'u, Etuini; Chan, Amy Hai Yan; Ryan, Brigid; Cullum, Sarah
Abstract : Objective: Estimates of dementia prevalence in New Zealand (NZ) have previously been extrapolated from limited Australasian studies, which may be neither accurate nor reflect NZ's unique population and diverse ethnic groups. This study used routinely collected health data to estimate the 1-year period prevalence for diagnosed dementia for each of the 4 years between July 2016 and June 2020 in the age 60+ and age 80+ populations and for the four main ethnic groups. Design: A population-based descriptive study. Setting: Seven national health data sets within the NZ Integrated Data Infrastructure (IDI) were linked. Diagnosed dementia prevalence for each year was calculated using the IDI age 60+ and age 80+ populations as the denominator and also age–sex standardised to allow comparison across ethnic groups. Participants: Diagnosed dementia individuals in the health datasets were identified by diagnostic or medication codes used in each of the data sets with deduplication of those who appeared in more than one data set. Results: The crude diagnosed dementia prevalence was 3.8%–4.0% in the age 60+ population and 13.7%–14.4% in the age 80+ population across the four study years. Dementia prevalence age–sex standardised to the IDI population in the last study period of 2019–2020 was 5.4% for Māori, 6.3% for Pacific Islander, 3.7% for European and 3.4% for Asian in the age 60+ population, and 17.5% for Māori, 22.2% for Pacific Islander, 13.6% for European and 13.5% for Asian in the age 80+ population. Conclusions: This study provides the best estimate to date for dementia prevalence in NZ but is limited to those people who were identified as having dementia based on data from the seven included data sets. The findings suggest that diagnosed dementia prevalence is higher in Māori and Pacific Islanders. A nationwide NZ community-based dementia prevalence study is much needed to confirm the findings of this study.